Role of long non-coding RNA-adducin 3 antisense RNA1 in liver fibrosis of biliary atresia. Issue 3 (1st March 2022) - Ye, Yongqin; Wu, Weifang; Zheng, Jiachen; Zhang, Lihui; Wang, Bin
ABSTRACT: Biliary atresia (BA) is a devastating liver disease in neonates. Liver fibrosis is regarded as a universal and prominent feature of BA. Studies have revealed that long non-coding RNAs (lncRNAs) regulate cellular processes during the development of liver fibrosis in BA. Long non-coding RNA-adducin 3 antisense RNA1 (lnc-ADD3-AS1) has been shown to increase susceptibility to BA. However, the role of lnc-ADD3-AS1 in liver fibrosis in BA remains unclear. Here, we investigated the role of lnc-ADD3-AS1 in the proliferation, migration, and apoptosis of the immortalized human hepatic stellate cell (HSC) line, LX-2. We successfully overexpressed and silenced lnc-ADD3-AS1 in LX-2 cells using adenovirus vectors and evaluated the proliferation of transfected cells using the Cell Counting Kit-8 (CCK8) assay. Cell apoptosis was detected using annexin V–fluorescein isothiocyanate (FITC)/propidium iodide (PI) double staining and flow cytometry. We then analyzed cell migration by performing wound-scratch and transwell migration assays. Our results show that lnc-ADD3-AS1 significantly promoted LX-2 cell proliferation and attenuated apoptosis. More importantly, lncRNA-ADD3-AS1 significantly accelerated the migration of LX-2 cells. Our data indicated that lncRNA-ADD3-AS1 plays a role in the pathogenesis of liver fibrosis in patients with BA and may serve as a potential diagnostic marker for monitoring liver fibrosis in BA or as a therapeutic target for the disease. graphical abstract: uf0001